MAGNETOLITHOLOGIC AND MAGNETOMINERALOGICAL CHARACTERISTICS OF DEPOSITS AT THE MESOZOIC/CENOZOIC BOUNDARY: GAMS SECTION (AUSTRIA) - Pechersky D.M.; Grachev A.F.; Nourgaliev D.K.; Tsel'movich V.A.; Sharonova Z.V. (My University, 2006)
This paper continues a series of detailed magnetolithologic and magnetomineralogical investigations of epicontinental deposits at the Mesozoic/Cenozoic (K/T) boundary and is devoted to the study of a small segment of the Gams section (Austria) including the K/T. Thermomagnetic analysis revealed several magnetic phases; according to the curve M(T), these are goethite ( T C = 90-150° C), hemoilmenite ( T C = 200-300° C), metallic nickel ( T C = 350-360° C), magnetite and titanomagnetite ( T C = 550-610° C), a Fe-Ni alloy ( T C = 640-660° C), and metallic iron ( T C = 740-770° C). Ensembles of magnetic grains has similar coercivity spectra in all samples and are characterized by a high coercivity. Against this background, the transition layer J with a maximum at 25-40 mT is identified, which is related to grains of metallic nickel and the Fe-Ni alloy. Numerous small (single-domain and superparamagnetic) grains of magnetic minerals present throughout the rock sequence contribute appreciably to the magnetic susceptibility of the rocks. With rare exceptions, the study deposits are anisotropic and have a mostly oblate magnetic fabric (foliation), indicating a terrigenous origin of the magnetic minerals. Many samples of sandy-clayey sediments have inverse magnetic fabric. This is primarily related to the inverse magnetic fabric of needle goethite that is present among the iron hydroxides. Relative contributions of paramagnetic (iron hydroxides, clays, and so on) and diamagnetic (carbonates and quartz) components in the sediments are estimated from M s values near 800° C, where the contribution of magnetic minerals is absent. Results of these studies imply that the K/T boundary is distinguished by a sharp rise in the concentrations of iron hydroxides and paramagnetic Fe-bearing minerals (it is at the K/T boundary, in the transition layer J, a sharp rise in the concentrations of magnetite and hemoilmenite occurs 4 cm above the K/T boundary). Lithologic control has no influence on the concentration of titanomagnetite, thereby reflecting the titanomagnetite dispersal at the time of eruptive activity that was most pronounced in the Maestrichtian. Metallic iron is distributed along the section rather uniformly, implying that it is most likely meteoritic dust. The occurrence of metallic nickel in the deposits is a unique phenomenon.
Keywords: MESOZOIC/CENOZOIC (K/T) BOUNDARY; MAGNETOMINERALOGY; LITHOLOGY; MAGNETIC MINERALS; PETROMAGNETOLOGY